Adipose Tissue T Cells in HIV/SIV Infection - Wanjalla, Celestine N.; McDonnell, Wyatt J.; Koethe, John R. (Frontiers in Immunology, 2018)
Adipose tissue comprises one of the largest organs in the body and performs diverse functions including energy storage and release, regulation of appetite and other neuroendocrine signaling, and modulation of immuity, among others. Adipocytes reside in a complex compartment where antigen, antigen presenting cells, innate immune cells, and adaptive immune cells interact locally and exert systemic effects on inflammation, circulating immune cell profiles, and metabolic homeostasis. T lymphocytes are a major component of the adipose tissue milieu which are altered in disease states such as obesity and human immunodeficiency virus (HIV) infection. While obesity, HIV infection, and simian immunodeficiency virus (SIV; a non-human primate virus similar to HIV) infection are accompanied by enrichment of CD8+ T cells in the adipose tissue, major phenotypic differences in CD4+ T cells and other immune cell populations distinguish HIV/SIV infection from obesity. Furthermore, HIV and SIV DNA and RNA can be detected in the stromal vascular fraction of visceral and subcutaneous adipose tissue, and replication-competent HIV resides in local CD4+ T cells. Here, we review studies of adipose tissue CD4+ and CD8+ T cell populations in HIV and SIV, and contrast the findings with those reported in obesity.